Legados de liberdade: alforrias testamentárias, poder e relações senhoriais (São Cristóvão, Sergipe, 1775 a 1850) - Farias, Nathiely Feitosa (2024)
This master’s thesis examined the decisions made by slave owners to manumit slaves in their testamentary bequests. Deciding to pursue the analysis of the testamentary manumission in those terms sets the debate in order to pay attention to the circumstances in which slaveholders deliberated about the manumission of slaves, with particular consideration to the experiences and expectations that affected those decisions. The historical research explores the sources available to the region of São Cristóvão, during the years of 1775 and 1850. Sources that include wills, inventories post-mortem and litigations about manumissions registered in the wills. The length of time selected to organize this study defines the moment when the province of Sergipe went through Nan intense expansion of sugar production. São Cristóvão, as a town, was placed in the center of the movements of the population’s growth, the reorganization of agrarian space, and, of course, the increase of slave labor’s demand. In this context, the slaves’ freedom cost slave owners a complex, well-considered and intentioned decision. Combining a quantitative survey and qualitative analysis, this master’s thesis reflects upon the manumission brought about in the wills’ bequests. What does it mean to trace an investigation guideline that starts with the elaboration of the will as a written document, and follows the pattern of the testamentary manumission, the conditions and justifications that endorsed the freedom bestowed, and finally ends with the analysis of the agreements and deals that have been settled earlier, in the personal space of the relation between slaves and masters, and that sustained the decision registered in the wills. Besides all the glances this line offers to understand the process of deliberate freedom of a slave, it also elucidates the most fundamental aspects of slavery in the province of Sergipe and the town of São Cristóvão, by the end of the eighteenth century and the first half of nineteenth century.